2018
DOI: 10.18280/ijht.360338
|View full text |Cite
|
Sign up to set email alerts
|

Thermal protection of rocket nozzle by using film cooling technology - effect of lateral curvature

Abstract: The present paper aims to analyze the applicability of film cooling method to a rocket as a thermal protection. Lateral curvature effect on film cooling performance through a single row of cylindrical holes with different spanwise angles is investigated. Four different lateral curvature cases (C = ∞, 100, 60, 20) with four inclination angles of cooling injection holes (β= 35°, 45°, 55°, 65°) are considered. The ANSYS CFX has been used for this computational simulation. The turbulence is approximated by a shear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In order to enhance film cooling effectiveness, new hole shape of film cooling (lidded hole) was proposed in the work of Guelailia et al [15]. The effects of surface radial and longitudinal curvature on the performance of film cooling was investigated by Guelailia et al [16,17]. Kumar et al [18] investigated the influence of cold flow injector of a rocket nozzle divergent section on film cooling effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance film cooling effectiveness, new hole shape of film cooling (lidded hole) was proposed in the work of Guelailia et al [15]. The effects of surface radial and longitudinal curvature on the performance of film cooling was investigated by Guelailia et al [16,17]. Kumar et al [18] investigated the influence of cold flow injector of a rocket nozzle divergent section on film cooling effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The heat transfer performance of showerhead film cooling as applied to the vane leading edge, and considering representative lean burn combustor swirling outflow was numerically investigated by Zhuang et al 15 Kouchih et al 16 numerically investigated several film cooling configurations including Barshan-dune-shaped shells, forward injection hole and backward injection hole. The influence of wall radial curvature on film cooling efficiency was numerically analyzed by Guelailia et al 17 A numerical study of swirling flow in coolant jets was conducted by ZHU et al 18 whose results demonstrated that film cooling effectiveness could be improved with jet swirl at high blowing ratios, and that swirl strength has significant influence on film cooling performance. The effects of mainstream turbulence intensity and blowing ratio on the endwall film cooling and heat transfer were numerically investigated by Yang et al 19 Results show that by increasing turbulence intensity, the variation of film cooling effectiveness was very limited.…”
Section: Introductionmentioning
confidence: 99%
“…The distinctness between gas turbine blades and rocket nozzles is the wall curvature. Turbine blade walls are curved in the stream-wise direction, and rocket nozzles walls can be curved in both stream-wise and span-wise directions [1]. Gas turbines are used extensively for aircraft propulsion, land-based power generation, and industrial applications.…”
Section: Introductionmentioning
confidence: 99%